MOLECULAR CHARACTERIZATION OF Aspergillus flavus TOXIGENICITY IN AGRICULTURAL COMMODITIES IN INDONESIA - Anidah, Anidah; Rahayu, Winiati P.; Nurjannah, Siti; Retnowati, Ina (BIOTROPIA, 2023)
Toxigenic Aspergillus flavus is a primary producer of aflatoxin in Indonesia, and its presence can lead to the contamination of agricultural commodities. This contamination poses a risk to export-targeted commodities, potentially resulting in their rejection. Therefore, this study aims to characterize the molecular profile of native A. flavus isolated from several Indonesian agricultural products, with a major focus on its toxigenicity and toxin production. A total of 18 A. flavus collections were isolated from nutmeg, ground peanut, cacao, coffee bean, corn, white pepper, and soil peanut plantation. Species identification was carried out using molecular and morphological approaches. The toxigenicity of isolates was characterized based on the amplification of aflatoxin gene clusters, while toxin production was assessed through growth simulation on a 10% coconut broth media followed by HPLC quantification. The result showed that all isolates were confirmed as A. flavus based on the morphological and sequence analysis of the ITS region. A total of 11 isolates (61%) were confirmed as toxigenic and produced 1-2 types of aflatoxin, in varying concentrations of high, moderate, or low levels of AFB1. High levels of AFB1 produced by seven isolates namely BIO3313, BIO33212, BIO3361, BIO33404, BIO3338, BIO3352, and BIO3344, had concentration levels ranging from 76.78 to 2241.06 µg/kg, while three isolates (BIO3314, BIO3312, and BIO3381) produced AFB1 below 1 µg/kg. Twenty-nine pairs of aflatoxin gene-specific sequences were successfully amplified as a single band, while some produced non-specific patterns in several low toxigenic and non-toxigenic isolates. Based on the results, it was concluded that completed gene clusters and variations of gene deletion were observed in both toxigenic and non-toxigenic isolates. However, no specific target gene could effectively distinguish the two groups. Two non-toxigenic isolates namely BIO3393 and BIO33403 exhibited a large deletion and could be potential candidates for biocontrol agents.